2020
DOI: 10.1186/s12889-020-8191-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motorcycle helmet types on head injuries: evidence from eight level-I trauma centres in Taiwan

Abstract: Background: Motorcycle full-coverage helmet use may reduce fatalities and head injuries. Methods: This retrospective cohort study extracted injury data from eight level-I trauma centres in Taiwan and performed a questionnaire survey to investigate injuries sustained by motorcyclists for the period between January 2015 and June 2017. Results: As many as 725 patients participated in the questionnaire survey and reported their helmet types or phone use during crashes. The results of multivariate logistic models d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 43 publications
5
43
4
1
Order By: Relevance
“…Accident victims who were not wearing crash helmet ended up being disabled and/or dead compared with those who wore crash helmet. These findings agree with previous studies [4,[16][17][18]. Other studies conducted in the USA [23] and India [24] reported similar findings to what was reported in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accident victims who were not wearing crash helmet ended up being disabled and/or dead compared with those who wore crash helmet. These findings agree with previous studies [4,[16][17][18]. Other studies conducted in the USA [23] and India [24] reported similar findings to what was reported in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Injuries to head and neck following motorcyclerelated accidents are common injuries which result in serious morbidity and mortality. Several studies are consistent that the use of crash helmet reduces the risk of head and neck injury severity among motorcycle users [4,[16][17][18]. The use of crash helmet is said to be very low in developing countries despite the existence of regulations that mandates its use [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head injury is more severe among those who wear non-standard helmet than those who wear standard helmet [7]. Evidence indicates that traumatic brain injury and impact during road crash decreases in standard as well as full-face helmet users [3,[8][9][10][11][12]. Full-face helmet provides facial protection in addition to head protection [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, using standard, full-face, and properly strapped helmet termed as effective helmet use is key to reducing injuries and deaths to greatest extent in motorcycle crash. Previous road side observational studies examined the prevalence and factors associated with helmet use (any helmet or proper helmet use) but none of them specifically studied use of full-face and properly strapped helmet [ 9 , 13 15 ]. With this background, we assessed prevalence and factors associated with effective helmet use among the motorcyclists in Mysuru, a tier II city in Southern India.…”
Section: Introductionmentioning
confidence: 99%